Does Financial Distress Contribute as an Intermediary Factor in Detecting Financial Statement Fraud ? - Saputra, Aditya Danang; Witono, Banu; Zulfikar, Zulfikar (SENTRALISASI, 2024)
This study aims to investigate whether financial distress acts as an intermediary factor in detecting fraudulent financial statements in manufacturing companies listed on the Indonesia Stock Exchange. The purposive sampling method was used to select 105 manufacturing companies during the period 2017-2021. The analysis was conducted using the Outer Smart PLS model to evaluate the relationship between auditor turnover, board turnover, financial targets, ineffective supervision, capability, and financial distress on financial statement fraud. The results confirmed that there was no significant influence between capacity, board turnover, financial targets, ineffective supervision, and financial distress on financial statement fraud. In addition, financial distress also does not mediate the effect of other variables on financial statement fraud. This approach reflects the ethical philosophy in the study that emphasizes honesty, integrity, and transparency in corporate financial reporting. These results highlight the importance of effective supervisory strategies and strong internal controls in preventing and detecting financial statement fraud, regardless of the company's financial distress. This study contributes by exploring the role of financial distress in detecting financial statement fraud. For future research, it is important to investigate additional factors that influence fraud and develop more effective monitoring strategies. Contingency theory emphasizes the importance of contextual factors in organizational management, while Fraud theory pays attention to the motives and driving factors behind fraudulent behavior.